(untitled) (Bangladesh Journal of Botany, 2025)
This study emulated the morphomolecular identification of Flavodon flavus (Kl.) Ryv. from the Chittagong University campus, Bangladesh. The morphological features of the fruit body of the fungus, such as the shape, size and texture of the basidiocarp, basidiome structure, surface characteristics of fruit body, spore-bearing surface of fruiting body, nature of the hymenophore, and dimitic hyphal system; absence of stipe and volva; nature of colony and microscopic features such as hyphal diameter, branching pattern, shape and size of spores corroborated the identity with Flavodon flavus. The identity of the fungus was further confirmed through sequencing and analysis of the internal transcribed spacer (ITS) region of nuclear ribosomal DNA (nrDNA). A BLASTn search of the ITS region sequences of this macrofungus revealed that the sequence was 97% similar to that of F. flavus. Bangladesh J. Bot. 54(2): 233-238, 2025 (June)